Mechanical comparison of six loop fixation methods with monofilament nylon leader line - Peycke, L. E.; Kerwin, S. C.; Hosgood, G.; Metcalf, J. B. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
Monofilament nylon leader line (MNL) is a popular prosthetic material used by veterinary surgeons for extra-capsular cranial cruciate ligament repair. Careful examination of MNL fixation methods has been reported, but a comprehensive comparison has not been done. This study evaluated three unpublished novel methods of MNL loop fixation [Harris wire tightener (knotter), Securos® crimp clamp system, self-locking knot] to traditional methods of MNL loop fixation (clamped square knot, sliding half hitch knot). Loops (27.3 kgt and 36.4 kgt) were distracted at 500 mm/min until failure by breaking or slipping. Ultimate force, elongation and stiffness were used for comparison of loop fixation methods. All of the loops failed by breaking within 3.0 mm of knot or clamp. The Harris knotter had significantly greater elongation than all other loops, except for the self-locking knot. The self-locking knot required the most force to failure; however, it was not superior if the doublestranded configuration was considered. If the mechanical properties of the knot method is considered in light of the subjective handling characteristics, the Securos® crimp clamp system had equivalent strength measurement for the 27.3 kgt MNL loops and was stronger than traditional methods using the 36.4 kgt MNL. The Securos® system recommends use of the larger diameter MNL and it allows a surgeon to overcome potential difficult handling characteristics previously encountered with knot formation and security.
Keywords: Ligatures; nylon